EEG-enhanced Prognostic Utility of Serum versus Cerebrospinal Fluid ESM-1 in Severe Traumatic Brain Injury - He, Lin; Wang, Yan; Ban, Jin; Wang, Jingsen; Kan, Shu; Li, Ju (Journal of Medical Biochemistry, 2025)
Objective: To analyze the differential prognostic value of serum versus cerebrospinal fluid (CSF) endothelial cell-specific molecule-1 (ESM-1), each combined with electroencephalogram (EEG), in patients with severe traumatic brain injury (sTBI), and provide a basis for optimizing the biomarker detection strategy for the disease. Methods: 98 sTBI patients (Glasgow Coma Scale [GCS] score ≤8) admitted from June 2023 to March 2025 were included. Serum and CSF samples were collected simultaneously from all patients after admission, and EEG monitoring was performed 48-72 hours post-injury. We employed enzyme-linked immunosorbent assay (ELISA) to measure serum ESM-1 and inflammatory factors (IL-6, TNF-α), and conducted chemiluminescence immunoassay (CLIA) to quantify CSF-ESM-1, S100β, and NSE. Multimodal EEG parameters were integrated with ESM-1 for joint modeling, with model efficacy in predicting 28-day mortality and adverse 6-month prognoses (defined as a GOS score of 1-3) evaluated by receiver operating characteristic (ROC) curve analysis. Results: Both serum and CSF-ESM-1 levels showed a positive correlation with inflammatory factors (IL-6, TNF-α) and BBB injury markers (S100β, NSE) (P<0.05). CSF-ESM-1 combined with EEG exhibited significantly superior predictive efficacy for 28-day mortality than serum ESM-1 + EEG, while also demonstrating better performance in predicting poor outcomes at 6 months. Conclusion: CSF-ESM-1, due to its direct reflection of the inflammatory-vessel injury microenvironment within the brain, has a significantly superior predictive efficacy when combined with EEG compared to serum ESM-1.